Work for a Better Future in Armenia : An Analysis of Jobs Dynamics - Honorati, Maddalena; Johansson de Silva, Sara; Millan, Natalia; Kerschbaumer, Florentin (World Bank, Washington, DC, 2020)
This report aims to provide a comprehensive package of timely and relevant input to the Government’s initiatives. In doing so, it brings together into one coherent framework and story-line both new analysis and previous work undertaken for the World Bank’s policy dialogue – in particular the Armenia Systematic Country Diagnostic and Drivers of Dynamism on constraints to growth, international integration, and poverty reduction, and the Skills Towards Employment and Productivity (STEP) surveys on the demand and supply of skills for the Armenian labor market.2 New analysis includes an updated view of the labor supply situation, labor productivity developments, and the links with recent overall macro and global trends. Because of data limitations, the demand side of the jobs agenda remains insufficiently explored, including analysis of the characteristics of job creating firms, the drivers of firm level productivity, and the constraints to firm growth, and hence to job creation. Ongoing data collection initiatives will help close these gaps over the short-to-medium term.